Hemoglobinopathies in newborns in the southern region of the Triângulo Mineiro, Brazil: Cross-sectional study - Carlos, Aline Menezes; Souza, Renata Andréia Volpe; Souza, Bruna Maria Bereta de; Pereira, Gilberto de Araujo; Tostes Júnior, Sebastião; Martins, Paulo Roberto Juliano; Moraes-Souza, Helio (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Hemoglobinopathies are among the commonest and most widespread genetic disorders worldwide. Their prevalence varies according to ethnic composition and/or geographical region. The aim of this study was to investigate the presence of hemoglobinopathies and their association with ethnicity among 1,004 newborns, to confirm the guideline of the Brazilian National Neonatal Screening Program. DESIGN AND SETTING: Cross-sectional study conducted in a public referral hospital in the Triângulo Mineiro region, Minas Gerais, Brazil. METHODS: Qualitative assessment of hemoglobin was performed through electrophoresis on cellulose acetate: at alkaline pH to identify the hemoglobin (Hb) profile and at acid pH to differentiate Hb S from Hb D and Hb C from Hb E and others that migrate to similar positions at alkaline pH. Neutral pH was used to detect Hb Bart’s identified in alpha thalassemia (α-thal). The elution method after electrophoresis was used to quantitatively assess hemoglobins. RESULTS: There was predominance of α-thal, with 105 cases (10.46%), followed by Hb S with 61 cases (6.08%, comprising 46 Hb AS, 2 Hb SS and 13 Hb S/α-thal), 9 cases (0.9%) of Hb AC and 6 cases (0.6%) suggestive of beta thalassemia (β-thal). The frequency of hemoglobinopathies was significantly higher among Afro-descendants. CONCLUSIONS: These findings corroborated of the National Neonatal Screening Program for diagnosing sickle cell disease and Hb C, Hb D, Hb E and β-thal hemoglobinopathies.